Outcomes of footprint medialization and bone marrow stimulation in chronic retracted rotator cuff tears - Hyoung Bok Kim; Seong Hun Kim (Clinics in Shoulder and Elbow)
Background This study compared the clinical and radiological outcomes of chronic retracted rotator cuff tears where complete footprint coverage cannot be achieved, using two treatments: footprint medialization with bone marrow stimulation and conventional incomplete repair. Methods This retrospective study included 87 patients who underwent arthroscopic rotator cuff repair with incomplete footprint coverage. The included patients were divided into group 1 (54 patients with footprint medialization and bone marrow stimulation) and group 2 (33 patients with conventional repair). Medialization and bone marrow stimulation were performed if the tendon did not cover a footprint of ≥1 cm2. Clinical outcomes, including a visual analog scale for pain score, range of motion, American Shoulder and Elbow Surgeons score, Constant-Murley score, and patient satisfaction, were evaluated preoperatively and at follow-up. Radiological healing was assessed using magnetic resonance imaging or computed tomography arthrography at 6 months and ultrasound at 2 years. Results Both groups showed significant improvements in clinical outcomes from preoperative levels. Group 1 demonstrated better outcomes in all measures at the final follow-up than group 2. Active range of motion improved significantly in both groups, with no significant postoperative differences. At 2 years postoperatively, group 1 had a significantly lower retear rate (14.8%) than group 2 (36.4%) (P=0.020). Conclusions In this study, the group that underwent footprint medialization and bone marrow stimulation for chronic retracted rotator cuff tears, in which complete footprint coverage was not possible, exhibited a lower retear rate and better clinical outcomes than the group that underwent conventional incomplete repair, with a minimum follow-up period of 2 years. Level of evidence III.